Case report: LAMC3-associated cortical malformations: Case report of a novel stop-gain variant and literature review - Falcicchio, Giovanni; Riva, Antonella; La Neve, Angela; Iacomino, Michele; Lastella, Patrizia; Suppressa, Patrizia; Sciruicchio, Vittorio; Trojano, Maria; Striano, Pasquale (Frontiers in Genetics, 2023)
Background. Malformations of cortical development (MCDs) can lead to peculiar neuroradiological patterns and clinical presentations (i.e., seizures, cerebral palsy, and intellectual disability) according to the specific genetic pathway of the brain development involved; and yet a certain degree of phenotypic heterogeneity exists even when the same gene is affected. Here we report a man with an MCD extending beyond occipital lobes associated with a novel stop-gain variant in LAMC3. Case presentation. The patient is a 28-year-old man suffering from drug-resistant epilepsy and moderate intellectual disability. He underwent a brain MRI showing polymicrogyria involving occipital and temporal lobes bilaterally. After performing exome sequencing, a novel stop-gain variant in LAMC3 (c.3871C>T; p.Arg1291*) was identified. According to the cortical alteration of the temporal regions, temporal seizures were detected; instead, the patient did not report occipital seizures. Different pharmacological and non-pharmacological interventions (i.e., vagus nerve stimulation) were unsuccessful, even though a partial seizure reduction was obtained after cenobamate administration. Conclusions. Our case report confirms that variants of a gene known to be related to specific clinical and neuroradiological pictures can unexpectedly lead to new phenotypes involving different areas of the brain.